2014
DOI: 10.1007/s10549-014-2856-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lymphedema after mastectomy: potential benefit of applying ACOSOG Z0011 protocol to mastectomy patients

Abstract: Purpose Axillary lymph node dissection (ALND) and radiation therapy (RT) are commonly recommended for mastectomy patients with positive sentinel lymph node biopsy (SLNB). Effective alternatives to ALND that reduce lymphedema risk are needed. We evaluated rates of lymphedema in mastectomy patients who received SLNB with RT, compared to ALND with or without RT. Methods 627 breast cancer patients who underwent 664 mastectomies between 2005–2013 were prospectively screened for lymphedema, median 22.8 months foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…Many studies have reported similar findings with increased risk of lymphedema with increase in number of lymph nodes removed, increased risk of lymphedema with greater extent of axillary surgery, decreased overall quality of life and arm function with greater extent of axillary surgery, and greater short and long-term morbidities with greater extent of axillary surgery. [5][6][7][8][9][10][11][12][13][14][15] Of note, there were patients in this study who had sentinel lymph node biopsy alone and still met criteria for intervention therefore rehabilitation referral decisions should not be based on absolute number of lymph nodes removed exclusively.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have reported similar findings with increased risk of lymphedema with increase in number of lymph nodes removed, increased risk of lymphedema with greater extent of axillary surgery, decreased overall quality of life and arm function with greater extent of axillary surgery, and greater short and long-term morbidities with greater extent of axillary surgery. [5][6][7][8][9][10][11][12][13][14][15] Of note, there were patients in this study who had sentinel lymph node biopsy alone and still met criteria for intervention therefore rehabilitation referral decisions should not be based on absolute number of lymph nodes removed exclusively.…”
Section: Discussionmentioning
confidence: 94%
“…Comorbidities impairing wound healing, such as renal disease, obesity, and malnutrition, predispose patients to unfavorable postoperative outcomes, including lymphedema. [15][16][17] Among operative characteristics, only the extent of axillary dissection influenced development of complicated lymphedema with an OR of 1.52 for formal axillary lymphadenectomy vs axillary node biopsy. This relationship is well corroborated by existing literature.…”
Section: Risk Factors For Lymphedemamentioning
confidence: 99%
“…Clinically apparent LE presents as visible or palpable tissue swelling, and diagnostic criteria for subclinical LE included a volume increase ‡ 3% in the affected upper limb measured by the Perometer compared with the patient's preoperative measurement and, with consideration of the contralateral limb volume changes or bioimpedance spectroscopy (BIS), uses resistance to low-frequency electrical current within the extracellular fluid compartment of limbs in order to determine volume differences. [12][13][14][15] The goal of timely intervention for breast cancer-related LE is decreased edema, smaller limbs, reduced joint aches, muscle pain and tightness, decreased infection rates, heightened patient desire to continue treatment, decreased medical costs, and improved quality of life. 6,[13][14][15] Various methods have been described to measure limb volume after the development of breast cancer-related clinical LE.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The goal of timely intervention for breast cancer-related LE is decreased edema, smaller limbs, reduced joint aches, muscle pain and tightness, decreased infection rates, heightened patient desire to continue treatment, decreased medical costs, and improved quality of life. 6,[13][14][15] Various methods have been described to measure limb volume after the development of breast cancer-related clinical LE. The standard modality involves tape-measuring limb circumference or water displacement, but both of these can be subject to wide variation as they are operator dependent.…”
Section: Introductionmentioning
confidence: 99%